The Effect of Visual Performance in Visually Impaired Patients on General Self-Efficacy, Depression and Quality of Life - A.R Heravian Shandiz; Sh Mesbahi; M Karimpour; M Tabe; A Sayadi (Journal of Paramedical Science and Rehabilitation)
Purpose:The purpose of this study was to investigate the impact of low vision on quality of life, general self- efficacy and depression in visually impaired people between the ages of 13 and 62 years.Methods:This research was applied in terms of purpose and causal-comparative in terms of execution. The study sample was 106 people with low vision and normal vision, who were divided into two groups (53 low vision and 53 normal sighted people) in a targeted way. Visually impaired people included 18 female and 35 male, and people with normal vision included 32 female and 21 male. The vision of normal and visually impaired people was measured by the examiner using the Snellen E chart. Data was collected using standard questionnaire of beck depression (1996), Sherer self-efficacy questionnaire (1982) and quality of life questionnaire related to vision (VFQ-25). Validity was calculated and confirmed by content validity method and reliability based on Cronbach's alpha coefficients for each of the questionnaires. The data were analyzed using t-test of two independent samples, Mann-Whitney test, Chi square test, Fisher’s exact test and multiples regression analysis variables with SPSS 22 software.Results:The results showed that visually impaired people have poorer visual performance than people with normal vision based on general self-efficacy, but this difference is not statistically significant (P>0.05). According to the results of the regression analysis, gender was one of the factors affecting the reduction of general self-efficacy on the visual performance of visually impaired people (P =0.02). Depression was reported more in the group of visually impaired people than in the group of people with normal vision, but this difference was not statistically significant (P>0.05). Using the results of the test, it was determined that the visual performance based on the quality of life in visually impaired people is lower than the visual performance in people with normal vision and there is a significant difference between the quality of life in the two groups of visually impaired and normal vision people (P=0.001).Conclusion:The results of this study showed that low vision is an effective factor in visual performance. Based on the findings of this study, the quality of life is considered to be an effective factor on the visual performance of visually impaired people. Therefore, the need to pay more attention to the psychological components of visually impaired patients is revealed.